(untitled) (Metallurgy and Foundry Engineering, 2016)
The paper presents the results of the structural type studies of resol phenolic resin used for the preparation of moulding and core sands exposed to the air. The FTIR study was carried out using a transmittance technique. Recorded changes in the IR spectra of resin can indicate a progressive polycondensation process, the consequence of which, among others, are changes in the aromatic rings of methylene bridges.